Іnteraction between a tubular beam of charged particles and an anisotropic dispersive solid-state cylinder - Averkov, Yu.O.; Prokopenko, Yu.V.; Yakovenko, V.M. (Вопросы атомной науки и техники, 2018)
The interaction between a tubular beam of charged particles and a nonmagnetic anisotropic dispersive medium of cylindrical configuration has been investigated. It has been found the absolute instability of bulk-surface waves that occurs because of peculiarities of the anisotropic cylinder properties. The resonance behavior of the permittivity frequency dependence causes the emergence of the sections of dispersion curves of the E-type bulk-surface eigenmodes with negative group velocity. It has been shown there are the E-type surface eigenmodes and pseudo surface eigenmodes of E- and H-types in the cylinder.